2010
DOI: 10.1068/p6527
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Recognition of Two-Dimensional Raised-Line Patterns by Early-Blind, Late-Blind, and Blindfolded Sighted Adults

Abstract: We investigated the role of visual experience and visual imagery in the processing of two-dimensional (2-D) tactile patterns. The performance of early-blind (EB), late-blind (LB), and blindfolded sighted (S) adults in the recognition of 2-D raised-line patterns was compared. We also examined whether recognition of 2-D tactile patterns depends on the type of memory strategy (eg spatial, visuo-spatial, verbal, and kinesthetic) used by EB, LB, and S participants to perform the task. Significant between-group diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
5
28
0
3
Order By: Relevance
“…Similarly, in a study of congenitally blind and sighted children, D'Angiulli, Kennedy, and Heller (1998) found that the congenitally blind children outperformed their sighted counterparts when both groups actively explored the tactile pictures. However, other studies have found either no difference in performance between blind and sighted participants (Ewart & Carp, 1963;Picard, Lebaz, Jouffrais, & Monnier, 2010) or that blind participants' recognition performance was worse than blindfolded sighted participants (Kennedy, 1993, pp. 57-59;Kennedy & Fox, 1977;Lederman, Klatzky, Chataway, & Summers, 1990).…”
mentioning
confidence: 99%
“…Similarly, in a study of congenitally blind and sighted children, D'Angiulli, Kennedy, and Heller (1998) found that the congenitally blind children outperformed their sighted counterparts when both groups actively explored the tactile pictures. However, other studies have found either no difference in performance between blind and sighted participants (Ewart & Carp, 1963;Picard, Lebaz, Jouffrais, & Monnier, 2010) or that blind participants' recognition performance was worse than blindfolded sighted participants (Kennedy, 1993, pp. 57-59;Kennedy & Fox, 1977;Lederman, Klatzky, Chataway, & Summers, 1990).…”
mentioning
confidence: 99%
“…In order to examine whether the auditory stimulus affected the tactile perception of roughness in terms of discrimination sensitivity or whether it simply biased participants to increase rougher or smoother responses, we quantified the discriminability and decision criterion by using A and B from the signal detection theory (see Grier, 1971;Komura et al, 2005;Picard et al, 2010) in the following analysis. These indexes were calculated using…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados das pesquisas comparativas envolvendo deficientes visuais e pessoas dotadas de visão normal são os mais diversos possíveis. Eles apontam desempenho inferior de deficientes visuais em relação a pessoas com visão normal (BAILES & LAMBERT, 1986;LEDERMAN et al,1990;HELLER et al, 2002), desempenho semelhante entre os dois grupos (MORRONGIELLO et al, 1994;PICARD et al, 2010) e também desempenho superior dos deficientes visuais em relação a pessoas de visão normal (HELLER, 1989;D´ANGIULLI et al, 1998). Além desta variedade de conclusões, ainda é possível apontar resultados em que há vantagem quanto ao desempenho de deficientes visuais com deficiência de início tardio sobre aqueles com deficiência visual precoce ou indivíduos dotados de visão normal (HELLER, 1989).…”
Section: Segundo Uma Das Principais Fundações Envolvidas Com a Deficiunclassified